2017
DOI: 10.2166/wst.2017.493
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification processes and microbial communities in a sequencing batch reactor treating nanofiltration (NF) concentrate from coking wastewater

Abstract: A biological denitrifying process was employed for the treatment of nanofiltration (NF) concentrate with high conductivity, which was generated from coking wastewater in a sequencing batch reactor (SBR). The results showed that the average removal efficiencies of chemical oxygen demand (COD), total nitrogen (TN) and nitrate were 47.6%, 61.1% and 94.6%, respectively. Different microbial communities were identified by sequencing the V1-V3 region of the 16S rRNA gene using the MiSeq platform, showing that the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Azoarcus Arenimonas , Planctomycetales_noname , Dechloromonas , and Rubrivivax were the dominant genera within the lake sediment surface. Such result have also been achieved in agricultural soils, activated sludge, landfi ll leachate and coking wastewater (Thomsen et al, 2007;Remmas et al, 2016;Coyotzi et al, 2017;Li and Lu, 2017). Out of the 36 genera identifi ed through nirS sequencing, six were not identifi ed at the level of genus.…”
Section: Eff Ects Of Organic Carbon Consumption On Denitrifying Bactementioning
confidence: 74%
“…Azoarcus Arenimonas , Planctomycetales_noname , Dechloromonas , and Rubrivivax were the dominant genera within the lake sediment surface. Such result have also been achieved in agricultural soils, activated sludge, landfi ll leachate and coking wastewater (Thomsen et al, 2007;Remmas et al, 2016;Coyotzi et al, 2017;Li and Lu, 2017). Out of the 36 genera identifi ed through nirS sequencing, six were not identifi ed at the level of genus.…”
Section: Eff Ects Of Organic Carbon Consumption On Denitrifying Bactementioning
confidence: 74%
“…NGS analysis further confirmed that the granules community was dominated by heterotrophic, nitrifying and denitrifying genera suggesting that shortcut nitrification-denitrification instead of PN/A process was established since the first weeks of operation. Chryseobacterium (genera containing species both capable of heterotrophic nitrification and aerobic denitrification [ 54 , 55 ]) was the most common genera (7.7–27.2%), while other dominant genera were Hylemonella (7.3–13.9%, denitrifiers [ 56 ]), followed by Nitrosomonas (9.9–14.0%, mainly nitrifiers [ 57 ]), Parvibaculum (7.0–11.7%, aerobic hydrocarbon-degrading bacteria and denitrifiers [ 58 , 59 ]), Rubrivivax (3.3–15.7%, involved in multiple biogeochemical and aromatic transformations, also denitrification, due to a wide metabolic capacity [ 58 , 60 ]) and other Comamonadaceae (4.3–8.9%, aromatic degraders and denitrifiers [ 61 ]), Chitinophagaceae (3.6–10.9%), other Saphrospirales (0.1–9.4%), Sphingopyxis (2.2–4.7%), other Burkholderiales (2.1–4.3%), Bdellovibrio (0.7–2.9%), Diaphorobacter (1.2–2.2%, both heterotrophic nitrifiers and denitrifiers [ 62 ]), Rhodanobacter (1.0–1.6%), the families of Alcaliganaceae (0.7–1.7%) and Xanthomonadaceae (0.8–1.1%), Clostridium (0.3–1.3%, biopolymers degraders able of N fixation [ 63 , 64 ]), Thermomonas (0.6–1.0%, denitrifiers [ 65 , 66 ]), Pseudomonas (0.0–1.4%, capable of both heterotrophic nitrification and/or aerobic denitrification [ 67 ]), and the family of Bradyrhizobiaceae (0.2–1.0%, N fixation [ 68 ]), other bacteria that singularly accounted for less than 1% of the total abundance were 7.6–14.3%.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the community structure of acetate and butyrate differed; Bacteroidetes, Firmicutes, Synergistetes, Cloacamonas, and Thermotogae were enhanced in AD, whereas Acidobacteria and Chloroflexi increased in BD (Figure 4b). Proteobacteria was the most abundant phylum in submerged macrophytes [29], a sequencing batch reactor for coking wastewater treatment [30], and a packed-bed bioreactor with a biodegradable polymer [31], whereas Bacteroidetes was the dominant phylum in a swing wastewater anaerobic reactor [32]. Interestingly, from the 2nd cycle of acetate, the microbial community structure was relatively similar to that of butyrate-assisted nitrogen removal in both nitrification and denitrification, as shown in the dendrogram (Figure 5a).…”
Section: Change Of the Microbial Community Under Consecutive Aerobic-anaerobic Conditions For Nitrification And Denitrificationmentioning
confidence: 86%